Self-reported pedestrian falls in 15 countries worldwide (2024)
Background Many factors are associated with pedestrian injuries and accidents. If a pedestrian is injured in an outdoor public space, we are talking about a “pedestrian fall”. Pedestrian falls are a more common cause of pedestrian injuries than traffic crashes but have received less attention and the literature on this topic is scarce. Aims and methods The aim of this work is to describe at a general level the prevalence and consequences of pedestrian falls and injuries, to make international comparisons of pedestrian falls and to identify risk factors and not least to examine the relationships between the prevalence of falls and pedestrian risk behaviour. A total of 6,373 participants from 15 different countries were recruited to take part in this study. To collect data a questionnaire was used. To cover the risky behaviour of pedestrians we used a short version of Pedestrians Behaviour Scale (PBS). In order to identify groups of countries with a similar pedestrian transport situation, a hierarchical cluster analysis was performed. The analysis produced four groups of countries based on pedestrians’ safety level, popularity of walking and GDP. Results and conclusions As for the results, we can conclude that young people and older people are more frequently involved in falls and that women report more frequent involvement in falls than males. However, the risk of getting injured in a fall is not higher than that of men. Frequent walking is associated with a lower risk of falling while walking. In contrast to this, physical activity increases such risk. The prevalence of falls and injuries seems to be weakly related to pedestrians’ risky behaviour, thus other factors such as safety infrastructure probably play an important role.